y= (x-2)^2+4 ....(1)
Solve for y from (2) divided by 2:
Substitute (2a) in (1)
7-2x = (x-2)^2+4
7-2x = x^2-4x+4+4
x^2 -2x +1 = 0 ....(1a)
Solve 1(a) to get:
x=1 (duplicity 2)
Now substitute x=1 in (2a) to get
Substitute x=1,y=5 in (1) to check:
(1-2)^2+4 = 5 OK.
Answer this Question
Geometry - How do solve the equations algebraically? x^2 + y^2 = 25 3y - 4x = 0
Math - We have an important chemsitry test due and I want to make sure that I do...
Algebra 2 - How do I do this f(x) = x - 5 (x + 4)^(1/2) when f(x) = -5 I know I ...
Algebra - Solve each inequality algebraically:how do I solve this problem? What ...
Math Gr 12 - We are learning to solve Factorable Polynomial Inequalities ...
pre-cal - How do I find the domain of the following function algebraically? I ...
math - Hi! I really need help with this question. Please help me. Thanks! If f(x...
solve algebraically - y=2x+6 x^2+y^2=8
math - geometry - graph the quadrilateral seperately nd algebraically and show ...
Math - Solve algebraically, 1/x=(x-34)/(2x^2).